Multiple oligomeric and conformational states of trypanosomatid phosphoglycerate mutases - Ahmad Fuad, Fazia Adyani (2013)
Parasitic protozoa from the order Trypanosomatida rely on glycolysis for their survival in mammalian hosts. As a consequence, the enzymes in the pathway are attractive chemotherapeutic targets. The seventh enzyme in the pathway, phosphoglycerate mutase (iPGAM), is of particular interest because it is structurally and biochemically completely different from the corresponding enzyme in humans.iPGAM is a monomeric, divalent metal-dependent enzyme whose two domains can exist in open and closed conformations. The closed-form crystal structure of Leishmania mexicana iPGAM has been solved, but the open conformation (currently unavailable) is particularly relevant for drug development, due to the poor accessibility of the enzyme’s catalytic site in the closed conformation. Ion-exchange chromatography has successfully separated the enzyme into several distinct oligomeric and conformational states: closed-form monomer (PI), open-form monomer (P2) and closed/open-form dimer (P3). A series of biophysical analyses, notably SEC-MALS, confirmed this observation by showing that P1 and P2 have similar masses of 58.2 and 59.1kDa, corresponding to monomeric LmiPGAM. However, the elution volumes in the SEC-MALS analysis differ by ~0.5 ml, indicating that the sizes and shapes of both samples are dissimilar, and are likely to indicate open and closed iPGAM conformations. In addition, P2 also contained a minor component with a mass of 114.9 kDa, consistent with the presence of dimeric iPGAM. P3 was relatively heterogeneous, and appeared to contain both the closed/open monomeric forms of iPGAM as well as the presence of a dimeric species. Furthermore, it was shown that divalent metals ions, particularly Co2+, affected the oligomeric states of iPGAM by causing all forms of the enzyme to be monomeric. It is thus suggested that the enzyme’s different conformational and oligomeric states are present at equilibrium in solution, an observation that is of particular relevance for further drug design and development.